2020
DOI: 10.1099/jmm.0.001179
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antivirulence activity of baicalin against Clostridioides difficile

Abstract: Introduction. Clostridioides difficile is an enteric pathogen that causes a serious toxin-mediated colitis in humans. Bacterial exotoxins and sporulation are critical virulence components that contribute to pathogenesis, and disease transmission and relapse, respectively. Therefore, reducing toxin production and sporulation could significantly minimize C. dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The limited reports available on the influence of selenium on ciprofloxacin effectiveness in vitro demonstrated that sodium selenite markedly enhanced the sensitivity of Clostridium difficile to ciprofloxacin leading to reduced bacterial growth in samples compared with antibiotic alone. [ 28 ] The greater effect of ciprofloxacin loaded selenium‐lipid nanoparticle in exterminating bacterial cells than the control has been attributed to its strong antimicrobial and antioxidant activities in the treatment of lung infection or diseases. [ 29 ] Moreover, coadministration of selenium and ciprofloxacin elicited a greater preventive effect on chronic bacterial prostatitis than ciprofloxacin alone in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The limited reports available on the influence of selenium on ciprofloxacin effectiveness in vitro demonstrated that sodium selenite markedly enhanced the sensitivity of Clostridium difficile to ciprofloxacin leading to reduced bacterial growth in samples compared with antibiotic alone. [ 28 ] The greater effect of ciprofloxacin loaded selenium‐lipid nanoparticle in exterminating bacterial cells than the control has been attributed to its strong antimicrobial and antioxidant activities in the treatment of lung infection or diseases. [ 29 ] Moreover, coadministration of selenium and ciprofloxacin elicited a greater preventive effect on chronic bacterial prostatitis than ciprofloxacin alone in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fecal C. difficile counts on day 6 were comparable across the challenged mice groups treated with or without BC (5a (iii)), there was a significant reduction in the fecal toxin-mediated Vero cell cytotoxicity in the CD+BC2 mouse group ( Figure 5 b(ii)). The reduced CDI severity in baicalin-treated mice could be attributed to the inhibitory effect of baicalin on C. difficile toxin production, as observed in our in vitro studies [ 31 ]. In addition, baicalin is known to possess anti-inflammatory and anti-diarrheal properties [ 34 , 35 , 36 ], which could also have contributed to the improved clinical outcome in BC-administered mice.…”
Section: Discussionmentioning
confidence: 54%
“…Previous research conducted in our laboratory revealed that sub-inhibitory concentration of baicalin reduced C. difficile toxin production and cytotoxicity in vitro. Additionally, baicalin inhibited C. difficile spore germination and outgrowth [ 31 ]. The results from the current study translate our previous findings in vivo by demonstrating a dose-dependent reduction of CDI severity in BC-supplemented mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations